2015
DOI: 10.1515/ract-2014-2316
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymer inclusion membranes containing T2EHDGA as carrier extractant for actinide ion uptake from acidic feeds

Abstract: Polymer inclusion membranes (PIM) containing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The increase in the metal ion uptake efficiency with increasing NPOE content can be explained considering the plasticization effect, which turns the membrane into a better medium for carrier and plasticizer movements, whereas the decrease in the uptake efficiency may be due to the plasticizer exudation, prevalent in the case of PIMs . We have noticed a similar decrease in the uptake efficiency of a T2EHDGA-based PIM in the presence of NPOE as a plasticizer at a much lower concentration (17.9–30.4%) . However, with all the PIMs with NPOE content in the range of 24.5–56.8%, the uptake of Am 3+ reached a near constant value of ∼88% after 24 h (Table S2, Supporting Information).…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…The increase in the metal ion uptake efficiency with increasing NPOE content can be explained considering the plasticization effect, which turns the membrane into a better medium for carrier and plasticizer movements, whereas the decrease in the uptake efficiency may be due to the plasticizer exudation, prevalent in the case of PIMs . We have noticed a similar decrease in the uptake efficiency of a T2EHDGA-based PIM in the presence of NPOE as a plasticizer at a much lower concentration (17.9–30.4%) . However, with all the PIMs with NPOE content in the range of 24.5–56.8%, the uptake of Am 3+ reached a near constant value of ∼88% after 24 h (Table S2, Supporting Information).…”
Section: Resultssupporting
confidence: 50%
“…However, as compared to solvent extraction systems, where a 100 times lower concentration of T-DGA (as compared to TODGA) was found to be enough, here a much larger concentration of T-DGA was required. The actinide uptake with the T-DGA-based PIMs follows the trend: Pu 4+ > Am 3+ ≫ UO 2 2+ > Th 4+ , which is slightly different (Am 3+ > Pu 4+ > Th 4+ ≫ UO 2 2+ ) from that reported with TODGA-containing PIMs but similar to that of T2EHDGA-containing PIMs . The sorption–desorption study indicated a limited use of the PIM as a sorbent.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations